Quality of life of individuals with stroke and their caregivers in a city of Triângulo Mineiro - Mary Lícia de Lima; Jair Lício Ferreira Santos; Namie Okino Sawada; Lívia Aparecida Pereira de Lima (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
Objective: To compare the quality of life (QoL) of individuals with stroke and their caregivers. Methods: This is an observational cross-sectional survey, involving 83 individuals who suffered a stroke. The participants were divided into four groups: group of individuals with stroke who have caregivers (44), group of individuals with stroke without caregivers (39), group of caregivers (44) and a reference group (83) in the period of March to May 2010. To assess QoL, the instrument used was the WHOQOL-bref. Results: The highest scores for the four fields were observed increasingly for the group of individuals with stroke with caregivers, the stroke group without caregivers followed by the group of caregivers and the reference group. The comparison of scores between groups showed that the presence of stroke and the fact of being caregiver affect QoL in all domains of WHOQOL-bref. Conclusion: It was possible to understand the negative impact that stroke causes in the lives of the affected ones and their caregivers, in order to better target public health policies.